Setting optimal diet ratios of kelp (Ecklonia maxima (Osbeck) Papenfuss) and formulated feed, and tests of a recirculating system using Ulva (Chlorophyta) as a biofilter, in South African abalone (Haliotis midae) cultivation - Sankar, Kishan (Department of Biological Sciences, 2015)
Includes bibliographical references (leaves 129-161).